Kejayaan modal Insan dan inovasi dalam pentadbiran mahkamah syariah: membina model antarabangsa - Wan Muhammad, Ramizah; Abdul Salam, Khairunnasriah (2019)
This article highlights the achievements of Shariah Courts in Malaysia in administering Islamic law especially on the issues of human capital as well as innovations which were introduced by the Department of Shariah Judiciary, Malaysia (JKSM) and the State Department of Shariah Judiciary (JKSN).also aims at fending off some negative notions against the Shariah Court as the second-class court in terms of power and achievements in administering and implementing Islamic law in Malaysia. The study uses qualitative approach and refers as well to the primary and secondary sources, which includes statutory provisions, monograf, articles, website information and interview with Tuan Haji Mohammad Syakir Abdul Hamid, the Registrar, JKSM at that time. The study found that the efforts made by JKSM/JKSN have, in the above-mentioned areas, achieved the goal and received recognition at the international level.